KAJIAN KARAKTERISTIK RUANG PARKIR SEPEDA MOTOR RODA DUA DI UNISKA MAB BANJARMASIN - Adhi Surya; Fathurrahman Fathurrahman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The research aims to get the description of the characteristics of two-wheeled parking at the Islamic University of Kalimantan Muhammad Arsyad Al Banjari (UNISKA MAB) Banjarmasin. For the long term get the arrangement of two-wheeled motor vehicle with a secure parking management and comfortable. The planned stages of the activity start from the problem, collecting secondary data to support the solution of the problem, conducting a study of literature studies that regulate parking, conducting field survey to get the primary data how many actual vehicle (SRP /unit parking area) so with the parking area limited can be given a solution and become a description of the characteristics of two-wheeled car park at UNISKA MAB Banjarmasin in the year of research 2017. Keywords: Motorcycle, SRP and Parking Space